Allergy to laboratory animals: an epidemiological study. Issue 1 (January 1992) - Aoyama, K; Ueda, A; Manda, F; Matsushita, T; Ueda, T; Yamauchi, C
Abstract : A large cross sectional survey was carried out using a self administered questionnaire to examine the prevalence of laboratory animal allergy (LAA) and the factors associated with its development. Out of 5641 workers who were exposed to animals at 137 laboratory animal facilities in Japan, 23.1% had one or more allergic symptoms related to laboratory animals. The commonest symptom as rhinitis. About 70% of LAA subjects developed symptoms during their first three years of exposure. Atopy (past and family history), the number of animal species handled, and the time spent in handling correlated significantly with the development of LAA as did some types of job. A close relation between nasal symptoms and exposure to rabbits and between skin symptoms and exposure to rats were found. LAA subjects developed symptoms most quickly to rabbits.